Analysis of Household Demand for Meat in Southwest, Nigeria (Global Journal of Science Frontier Research, 2012)
This study investigated household demand for meat in some selected states in the Southwest Nigeria. The systematic sampling technique was used to select two hundred and forty household in the study area and data were collected through well structured questionnaire. Analysis was done using Descriptive Statistics and Almost Ideal Demand System (AIDS) Model. The findings showed that beef (43.7%) was mostly preferred in the study area, income levels of respondents and taste influenced the type of meat preferred. The budget share of beef decreased with an increase in the price of chicken and vice versa, but increased with an increase in its price, the budget share of chevon , chicken and mutton increased with an increase in their own prices respectively. The budget share of pork increased with an increase in the price of mutton but it decreased with an increase in its own price.. Also one percent change in prices of beef,chevon and chicken would result in -0.827, -0.527 and -0.721 reduction in the quantity demanded respectively. Mutton and pork were confirmed to be luxury goods while chicken, beef and chevon were normal goods for households in southwest, Nigeria. Price intervention programmes should be introduced in order to stabilize the fluctuation in meat prices
Keywords: Meat; household demand; pork; mutton; beef; chevon; chicken; elasticity; price; Southwest; Nigeria